Autecology and embryology of Audouinia capitata (Bruniaceae), a threatened species in the Cape floristic region - De Lange, Johannes Hendrik (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.